2016
DOI: 10.1007/s00428-016-2056-0
|View full text |Cite
|
Sign up to set email alerts
|

Value of postmortem studies in deceased neonatal and pediatric intensive care unit patients

Abstract: Worldwide, various autopsy studies have shown a decrease in the diagnostic error rate over the last years. The cause of this positive development is mainly due to the improvement of modern medicine. However, intensive care unit patients are thought to have a higher risk for diagnostic errors, which is documented in several studies in the adult population. In contrast, there is only limited information about diagnostic errors in pediatrics, particularly in pediatric and neonatal intensive care units. The aims o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Another study enrolled 35 infants younger than 4 months of age with an acute illness of suspected genetic cause in NICUs or paediatric intensive care units (PICUs), and identified 21 (60%) infants with a genetic disorder 35. Several studies concerned with death in NICUs have demonstrated the causes and clinical characteristics of death in neonates,36 end-of-life care practices and decisions,37 as well as the value of postmortem autopsy 38. However, genetic causes of death in NICUs are less frequently reported.…”
Section: Discussionmentioning
confidence: 99%
“…Another study enrolled 35 infants younger than 4 months of age with an acute illness of suspected genetic cause in NICUs or paediatric intensive care units (PICUs), and identified 21 (60%) infants with a genetic disorder 35. Several studies concerned with death in NICUs have demonstrated the causes and clinical characteristics of death in neonates,36 end-of-life care practices and decisions,37 as well as the value of postmortem autopsy 38. However, genetic causes of death in NICUs are less frequently reported.…”
Section: Discussionmentioning
confidence: 99%
“…Reports in other NICUs range from 20.3 to 82% [2, 4]. Additional findings determined by autopsy (class I–IV) were encountered in 48% of the cases, consisting of major (24%) and minor (24%) additional findings, also referred to as diagnostic errors.…”
Section: Discussionmentioning
confidence: 99%
“…Since clinical manifestations of conditions in newborn infants are often nonspecific [2], unintentionally delayed, wrong, or missed diagnoses are still inevitable. In the literature, the latter are defined as diagnostic errors [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 To date, however, the few studies on diagnostic errors in the NICU have been autopsy-based evaluations that did not assess nonlethal diagnostic errors. 4 5…”
mentioning
confidence: 99%